Description of new taxa of Nymphalidae (Lepidoptera: Papilionoidea) from China - Tshikolovets, Vadim (Zootaxa, 2017)
Three new taxa, Clossiana gansuensis sp. nov., Euphydryas aurinia sichuanica subsp. nov. and Chalinga puerensis sp. nov. are described from Yunnan, Gansu and Sichuan Provinces in China. The taxonomic status of Euphydryas aurinia tenebricosa (Bang-Haas, 1927) is revised.